Electric Field Induced Raman Scattering at the Sb–InP(110) Interface: The Surface Dipole Contribution. Issue 2 (26th September 2018) - Esser, Norbert; Schmidt, Wolf‐Gero
Abstract : Using the prototypical interface of Sb on InP(110), it has been shown that strong local electric dipole fields may arise at semiconductor surfaces which need to be considered in addition to band bending‐induced electric fields for explaining electro‐optic effects. Symmetry forbidden LO phonon Raman scattering, which has been often used in the past to analyze internal electric fields related to band bending, is a suitable optical probe. The surface local dipole field, related to reconstruction or relaxation‐dependent atomic displacements in the outermost atomic planes, delivers a significant contribution to the forbidden LO phonon scattering, in addition to the band bending‐related Schottky field. Taking this into account, apparent inconsistencies of the electric field‐induced Raman scattering (EFIRS) and photoemission spectroscopy from the previous work can be resolved. Abstract : Surface potentials of the ideal, relaxed, and Sb‐monolayer terminated InP(110) surface are compared. A redistribution of electronic charge within the uppermost two atomic (110) planes goes along with surface relaxation and induces a strong electric dipole field at the surface. As shown in this article, the local surface field gives rise to electric field‐induced LO phonon scattering in the substrate.